Atomic-scale insights into the interfacial instability of superlubricity in hydrogenated amorphous carbon films - Chen, Xinchun (Sci Adv, 2020)
The origin of instability or even disappearance of the superlubricity state in hydrogenated amorphous carbon (a-C:H) film in the presence of oxygen or water molecules is still controversial. Here, we address this puzzle regarding the tribochemical activities of sliding interfaces at the nanoscale. The results reveal that gaseous oxygen molecules disable the antifriction capacity of a-C:H by surface dehydrogenation of tribo-affected hydrocarbon bonds. In comparison, oxygen incorporation into the hydrocarbon matrix induces the formation of a low-density surface shear band, owing to which the friction state depends on the oxygen content. High friction of a-C:H film in humid environment originates from the “tumor-like” heterogeneous structures as formed in the highly oxidized tribolayer. Notably, an appropriate doping of silicon can completely shield the moisture effect by forming a silica-like tribolayer. These outcomes shed substantial lights upon the roadmap for achieving robust superlubricity of carbon films in a wide range of environments.